(3GdfXQjI h GdJWHjbs - (3MQHj eMeO(B, (3YQjbGJs; (3SYjO LeYI Ybd(B, s ((3YeGf(B:s (3OGQ hGFd(B,s, 2008)
(3GdNWQ eagheg h CTcGdg , eaGgje CSGSjI aj GdJCejf hhXGFag , GdCQcGf h GdejGOF GdbGfhfjI dYbO GdJCejf , CfhGY GdJGejfGJ GdYGeI , GdJCejf GdHMQj , JCejf GdSjGQGJ , EYGOI GdJGejf , GdJCejf GdGSdGej , JMOjO CbSGW GdJCejf , GdJShjb GdJCejfj , GdVeGf GdGLJeGYj , GdJCejf GdUMj , GdJCejf Ydi GdMjGI , GdTQhW GdCSGSjI aj hKjbI GdJCejf Ydi GdMjGI , CfhGY GdJGejf Ydi GdMjGI , Shb GdJCejf aj GdCQOf JWhQg hgjcdg(B.s
(3eQGLY U(B.481s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdeNGWQs; (3eNGWQ GdegfIs